The transcription factor HLH-26 controls probiotic-mediated protection against intestinal infection through up-regulation of the Wnt/BAR-1 pathway. - Yu Sang; Jie Ren; Alejandro Aballay (PLoS Biology, 2022)
Probiotics play a critical role in the control of host intestinal microbial balance, protecting the host from gastrointestinal pathogens, modulating the host immune response, and decreasing host susceptibility to infection. To understand the mechanism underlying the protective effect of probiotics against infections through immune regulation, we examined protection against Salmonella enterica infection following exposure to nonpathogenic Enterococcus faecium in the nematode Caenorhabditis elegans. We found that the transcription factor HLH-26, a REF-1 family member of basic helix-loop-helix transcription factors, was required in the intestine for E. faecium-mediated protection of C. elegans against a lethal S. enterica infection. In addition, we uncovered that defense response genes controlled by the canonical Wnt/BAR-1 pathway were activated upon exposure to E. faecium in an HLH-26-dependent manner. Our findings highlight a role for REF-1/HLH-26 in the control of the Wnt/BAR-1 pathway in probiotic-mediated protection against gut infection.